Brucine-Loaded Nanoparticles: Advancements in Targeted Drug Delivery Systems - Priyanka, Mandal; Nilakshi, Dhoble; Nitin, Padole; Pankaj, Dhapke; Jagdish, Baheti (Asian Journal of Pharmaceutical Research and Development, 2024)
Brucine-loaded nanoparticles represent a significant advancement in drug delivery systems, leveraging the pharmacological properties of brucine, an alkaloid derived from the Strychnos nux-vomica plant. This study aimed to develop and assess the efficacy of brucine-loaded nanoparticles in advancing drug delivery systems. Nanoparticles, as carriers, offer a versatile platform for controlled and targeted drug delivery. They were meticulously crafted using biocompatible materials and thoroughly characterized for their physicochemical attributes, drug loading efficiency, and release kinetics. Techniques such as UV spectroscopy, Fourier-transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), field-emission scanning electron microscopy (FESEM), and differential scanning calorimetry (DSC) were employed for comprehensive characterization. Surface modification with targeting ligands facilitated the precise delivery of brucine to specific cells or tissues, thereby enhancing therapeutic efficacy while minimizing off-target effects. studies provided valuable insights into the biodistribution and pharmacokinetics of the nanoparticles, underscoring their potential in advancing drug delivery systems. Overall, the findings highlight the significant role of brucine-loaded nanoparticles in advancing drug delivery systems, promising remarkable advancements in nanoparticle-based therapeutics.